Financial Management from an Emerging Market Perspective - Kucukkocaoglu, Guray; Gokten, Soner (IntechOpen, 2018)
One of the main reasons to name this book as Financial Management from an Emerging Market Perspective is to show the main differences of financial theory and practice in emerging markets other than the developed ones. Our many years of learning, teaching, and consulting experience have taught us that the theory of finance differs in developed and emerging markets. It is a well-known fact that emerging markets do not always share the same financial management problems with the developed ones. This book intends to show these differences, which could be traced to several characteristics unique to emerging markets, and these unique characteristics could generate a different view of finance theory in a different manner. As a consequence, different financial decisions, arrangements, institutions, and practices may evolve in emerging markets over time. The purpose of this book is to provide practitioners and academicians with a working knowledge of the different financial management applications and their use in an emerging market setting. Six main topics regarding the financial management applications in emerging markets are covered, and the context of these topics are "Capital Structure," "Market Efficiency and Market Models," "Merger and Acquisitions and Corporate Governance," "Working Capital Management," "Financial Economics and Digital Currency," and "Real Estate and Health Finance."